(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
This article aims to examine judges’ considerations on marriage dispensation cases, whether using human rights values and norms or local norms. The article discusses challenges posed to implementing human rights values and norms, including child rights in such instances, especially in the Central Java Religious Court. Supporting data consists mostly of court decisions and interviews with judges at three Islamic courts in Central Java. The research reveals that most of the judges’ legal considerations in granting marriage dispensation apply the foundation of the local norms (Adat/customary law), Islamic Law, and national legislation related to marriage, but lacks reference to human rights norms.